1996
DOI: 10.1111/j.1467-8535.1996.tb00141.x
|View full text |Cite
|
Sign up to set email alerts
|

Information access and retrieval with hypermedia information systems

Abstract: Students' success with interactive information systems (11s) such as those found in many CD-ROM applications depends to large degree on their capacity accurately to choose and apply search strategies in response to information needs. 11s systems provide many ways to retrieve information, with some methods being more efficient and effective than others. The purpose of this study was to investigate the search strategies employed by novice users of an 11s system and to analyse the problems and issues that were im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

1999
1999
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 14 publications
0
10
0
2
Order By: Relevance
“…However, as the number of links goes up, the structure of a hypertext becomes more fragmentary. The consequences of a fragmented structure are: cognitive overload, navigation inefficiency and disorientation (Conklin, 1987;Gärling and Golledge, 1989;Oliver and Oliver, 1996;Van Nimwegen et al, in press). To avoid these negative effects, researchers recommend-among other thingsan interface with a structural overview of the links between sections (Jonassen, 1986;Halasz and Conklin, 1989;Heller, 1990;Thüring et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…However, as the number of links goes up, the structure of a hypertext becomes more fragmentary. The consequences of a fragmented structure are: cognitive overload, navigation inefficiency and disorientation (Conklin, 1987;Gärling and Golledge, 1989;Oliver and Oliver, 1996;Van Nimwegen et al, in press). To avoid these negative effects, researchers recommend-among other thingsan interface with a structural overview of the links between sections (Jonassen, 1986;Halasz and Conklin, 1989;Heller, 1990;Thüring et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…They are likely to under-specify the problem, be distracted by irrelevancies, be unsure how to evaluate the information they find, over-generalise from specific instances, be unaware of incompleteness, or fail to recognise inconsistencies (Laurillard, 1995). Teacher input will be needed in the form of preparation, supervision and de-briefing (Kobayashi, Sasaki and Takeya, 1997;Oliver and Oliver, 1996). This observation was confirmed in the IMPS project ± by one teacher who found it particularly helpful to have large group sessions that introduced pupils to computer conventions and procedures, and by another who found that her most effective worksheets were those that combined navigational prompts with those about content.…”
Section: Methodsmentioning
confidence: 99%
“…using contents pages and indexes) are taken for granted and should be made more explicit by those concerned with improving children's literacy skills.' (p. 144) Oliver and Oliver (1996) noted that 12-year-old children's previous levels of computer experience and computer confidence affected the range of search options and features that they chose to use. The more experienced children also tended to experiment more and to devise short cuts, while others tended to continue to re-apply a strategy that had worked before.…”
Section: Searching and Retrievingmentioning
confidence: 99%
“…Marchionini (1989a) also comments on youngsters' entry of actual sentences and natural language to query the system, and Large, Beheshti and Breuleux (1998) found that their youngsters often merely employed words used by their teachers to describe their topics. In several studies a browsing approach has been seen to predominate (Marchionini, 1989a; Oliver & Oliver, 1996; Large, Beheshti, & Breuleux, 1998), yet Bland's (1995) teenagers recognized the need to combine keywords to increase search effectiveness. Users scrutinized by Large et al (1994) readily experimented with the search routes offered by the system.…”
Section: Related Researchmentioning
confidence: 99%
“…Youngsters of various ages sampled by Marchionini (1989a, b) readily accepted basic system settings and ignored more sophisticated search options. A further recurrent theme appears to be the tendency of inquirers to employ a favored strategy repeatedly, even if it is not delivering the desired results (Oliver & Oliver, 1996; Large, Beheshti, & Breuleux, 1998).…”
Section: Related Researchmentioning
confidence: 99%